Association between impaired brachial flow-mediated dilation and early neurological deterioration in acute ischemic stroke: a retrospective analysis - Sang Hee Ha; Bo Hye Yoon; Bon Gook Koo; Dong Hoon Shin; Yeong-Bae Lee; Bum Joon Kim (BMC Neurology)
Abstract Background Early neurological deterioration (END) occurs in individuals who had experienced acute ischemic stroke (AIS), impacting long-term functional outcomes. We aimed to investigate the association between endothelial function, measured via flow-mediated dilation (FMD), and END in patients with AIS. Methods We retrospectively reviewed patients who had experienced AIS within 7 days of stroke onset and underwent FMD assessments during their hospitalization (%FMD = Peak diameter − baseline diameter)/baseline diameter x 100). END was defined as ≥ 2-point increase in the National Institutes of Health Stroke Scale total score or ≥ 1-point increase in the motor score within 72 h post-stroke. Through multivariate analysis, we examined factors associated with END and explored the relationship between FMD and END with considering stroke mechanisms. Results Among 1,262 patients diagnosed with AIS, 184 (14.6%) experienced END. Those with END were on average older (69 ± 13 vs. 67 ± 13 years; P = 0.033), had a higher prevalence of stroke history (21.2 vs. 12.9%; P = 0.003), and lower FMD (5.0 ± 1.8 vs. 5.4 ± 2.2%; P = 0.029). Multivariate analysis revealed that a history of stroke (adjusted odds ratio [aOR] = 1.728; 95% confidence interval [CI] 1.159–2.578; P = 0.007) and low % were independently associated with END. Subgroup analysis revealed that low %FMD was significantly associated with END within the small vessel disease (SVD) category (aOR = 0.789; 95% CI 0.679–0.920; P = 0.002). Conclusions Impaired FMD may be associated with END, particularly within the context of SVD.